Innovative methods of ethno-cultural competence development on the basis of Kazakh stories - Panzabek, Bagila; Zhumakayeva, Bereke; Ibragimova, Zhanat; Tolysbayeva, Ademau; Akimisheva, Zhanar (Opción, 1970)
The purpose of the article is to prove that multilingual education is a universal matrix of dimensions, qualities, and approaches that encompass theories and practices of educational reform. On the basement of our methodology, we presented four stages of ethno-cultural competence development in teaching Kazakh literature for Russian-speaking students of higher educational institutions. Each stage fulfills its own specific functions and the set of certain skills are formed on each stage, which is equipped by the most effective methods and techniques. Experiment showed that the usage of methodology promoted the effective acquisition by ethno-cultural competence by students through Kazakh stories.